A leitura e a escrita na primeira etapa da educação infantil: os discursos e as práticas pedagógicas - Souza, Lilian Silva de Lucas de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The purpose of this dissertation is to focus on teaching practices related to children's interaction with the literate world. Such practices were performed in early childhood education, which cater to children aged zero to three years old. During the research, we verified the conceptions of teaching and learning how to read and write, which play a dominant role in educators' practices and speeches. Initially, we present a brief history of this mode of education. Following, we focus on the most common epistemological conceptions in teaching, so we can later analyze the teaching practices and their implications in the process of learning to read and write. The research was carried out in the Municipality of Rio Claro, SP, Brazil. The municipal schools were chosen according to their classification into three large groups: big schools (12 classrooms); medium-sized schools (six classrooms) and small schools (four classrooms). After this classification, one school of each group was picked according to the Fisher-Yates Shuffle (1957), totaling 18.75% of day-care centers in the Municipality. Seventeen educators participated in the research: six teachers and 11 teaching assistants. Data was collected by observing classes and interviewing the educators. The observations were registered in a field log and audio recordings. The interviews were performed at times arranged with the participants, and they were also recorded and, then, totally transcribed. The collected and analyzed data showed that the reading and writing-related didactic approaches observed in the classroom are based on the conceptions of either the empiricist or aprioristic epistemology. Four out of the six participating teachers presented innovating activities in their practices. Both the assistants' and the teachers' speeches showed a mixture of conceptions, thus demonstrating a contradiction between their practice and ... (Complete abstract electronic access below)

Esta dissertação focaliza as práticas pedagógicas, referentes às interações das crianças com o mundo letrado, práticas essas realizadas na primeira etapa da educação infantil, que atende crianças de zero a três anos de idade. Em pesquisa buscamos averiguar, as concepções de ensino e de aprendizagem da leitura e da escrita, preponderantes nas práticas e nos discursos das educadoras. Inicialmente apresentamos um breve histórico dessa modalidade de ensino. A seguir focalizamos as concepções epistemológicas mais presentes no ensino para posterior análise das práticas pedagógicas e suas implicações no processo de aprendizagem da leitura e da escrita. A pesquisa foi realizada no município de Rio Claro - SP e a escolha das escolas municipais se deu por meio de uma classificação das mesmas em três grandes grupos: escolas grandes (com 12 salas de aulas), escolas médias (6 salas) e escolas pequenas (4 salas). Após esta classificação, uma escola de cada grupo foi sorteada de acordo com a tabela de Fisher e Yates (1957), totalizando 18,75% das creches do município. Participaram da pesquisa seis professoras e 11 monitoras inteirando 17 educadoras. A coleta de dados deu-se por meio das observações das aulas e de entrevistas com as educadoras. As observações foram registradas em diário de campo e gravação de áudio. As entrevistas foram feitas em momentos indicados pelas participantes e também gravadas em áudio e, depois, transcritas integralmente. Os dados coletados e analisados revelaram que a maioria dos encaminhamentos didáticos, observados, que focam a leitura e a escrita, em aulas, baseiam-se nas concepções epistemológicas empirista ou apriorista. Das seis professoras participantes da pesquisa quatro apresentaram em suas práticas, atividades consideradas inovadoras. Os discursos tanto das monitoras quanto os das professoras mostraram uma mistura, ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Educação pre-escolar; Leitura; Escrita; Alfabetização; Education, Preschool; Rio Claro (SP)